2019
DOI: 10.1177/0300060519879006
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-guided biopsy of small lung nodules: diagnostic accuracy and analysis for true negatives

Abstract: Objective We evaluated the diagnostic accuracy of computed tomography (CT)-guided transthoracic core needle biopsy (TCNB) for small (≤20-mm) lung nodules and identified predictive factors for true negatives among benign biopsy results. Methods From March 2010 to June 2015, 222 patients with small lung nodules underwent CT-guided TCNB. We retrospectively analysed data regarding technical success, diagnostic accuracy, and predictors of true negatives. Results The technical success rate was 100%. The TCNB results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(49 reference statements)
2
11
0
Order By: Relevance
“…First of all, the NPV in the training group of this study was 85.4%, which is within the range demonstrated by previous studies regarding CT-guided CNB for lung lesions (78−90%) [9,10,12].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…First of all, the NPV in the training group of this study was 85.4%, which is within the range demonstrated by previous studies regarding CT-guided CNB for lung lesions (78−90%) [9,10,12].…”
Section: Discussionsupporting
confidence: 87%
“…Abnormal tumor marker levels were not found to be associated with false-negative results, although univariate logistic analysis demonstrated that abnormal CEA and SCC levels were predictors of falsenegative results. Also previous studies did not find any tumor marker level to be associated with false-negatives from CNB-based benign results [9,10,12].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…CT‐TTNB was commonly associated with complications including pneumothorax and hemorrhage. Risk factors associated with CT‐TTNB adverse outcomes include a longer distance to the pleura, the number of needle pathways used, and the position of the patient during biopsy 29,30 . In contrast, the EBUS approach is conducted in the bronchial lumen, thereby avoiding damage to the lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%